2015
DOI: 10.1080/10511970.2015.1046005
|View full text |Cite
|
Sign up to set email alerts
|

Inquiry-Based Learning and the Flipped Classroom Model

Abstract: The flipped classroom model of teaching can be an ideal venue for turning a traditional classroom into an engaging, inquiry-based learning (IBL) environment. In this paper, we discuss how two instructors at different universities made their classrooms come to life by moving the acquisition of basic course concepts outside the classroom and using class time for active problem-based learning. Results from student surveys are presented to relate student perceptions of the flipped/IBL classroom model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 17 publications
4
41
0
1
Order By: Relevance
“…This implies that students in a group learning situation are the best way to foster critical thinking or higher-order thinking skill. This finding of this study was also alike with the results reported that the flipped classroom instruction enables students to get out of their seats and interact with each other, to build learning communities and exchange ideas to solve problems (Kim et al, 2014;Love, Hodge, Corritore, & Ernst, 2015;Little, 2015;Sun & Wu, 2016). This can be assumed that the more interactive individuals perceive themselves in activities, the more intrinsically motivated they will be.…”
Section: Discussionsupporting
confidence: 84%
“…This implies that students in a group learning situation are the best way to foster critical thinking or higher-order thinking skill. This finding of this study was also alike with the results reported that the flipped classroom instruction enables students to get out of their seats and interact with each other, to build learning communities and exchange ideas to solve problems (Kim et al, 2014;Love, Hodge, Corritore, & Ernst, 2015;Little, 2015;Sun & Wu, 2016). This can be assumed that the more interactive individuals perceive themselves in activities, the more intrinsically motivated they will be.…”
Section: Discussionsupporting
confidence: 84%
“…Such changes could happen in any subject matters if teachers were not restricted to the goals and content of the National Curriculum which cannot be easily covered within the constraints of classroom time with the students. One of the most promising ways to cover the required content and also benefit from IBL-based instruction may be the combination of this teaching method with the FC approach (Love et al, 2015) or the use of IBL features within a FC instruction (Chen & Chang, 2017;Huang & Lin, 2017;Çakiroglu & Özturk, 2017). One such example is Chen and Chang's (2017) research in higher education context using the SOP² model into the flipped classroom ("S": Self-study, "O": online group discussion, and "P2": Double-stage Presentations).…”
Section: Flipped Classroom Research-a Challenge For Primary Educationmentioning
confidence: 99%
“…It is also referred to as inverted classroom (Gannod, Burge, & Helmick, 2008). It is the model where the traditional lecture materials are transferred outside the classrooms (in alternative formats, mainly video-tutorials, readings, screencasts), allowing in-class time to be used for collaborative Inquiry-Based Learning (IBL) activities (Bergmann, & Sams 2015;Love et. al., 2015;Ullman, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In order for this and other "inquirybased" methods to work optimally, students need to ask each other good questions, which they often have never learned to do, so some instructors have tried intentionally modeling asking good questions as scaffolding to guide students to ask them on their own [1]. Many instructors have found success using the "flipped classroom" model, where students prepare for class by learning the material on their own via textbook, slides or video lectures, and then spent class time solving math problems, playing content-specific games, or doing computer programming [8]. For a comparison of the "flipped classroom" versus "inquiry-based learning" teaching methods, and methods of combining the two, see [3].…”
Section: Introductionmentioning
confidence: 99%